2021
DOI: 10.1038/s41598-020-77756-x
|View full text |Cite
|
Sign up to set email alerts
|

Spin and pseudospin solutions to Dirac equation and its thermodynamic properties using hyperbolic Hulthen plus hyperbolic exponential inversely quadratic potential

Abstract: In this research article, the modified approximation to the centrifugal barrier term is applied to solve an approximate bound state solutions of Dirac equation for spin and pseudospin symmetries with hyperbolic Hulthen plus hyperbolic exponential inversely quadratic potential using parametric Nikiforov–Uvarov method. The energy eigen equation and the unnormalised wave function were presented in closed and compact form. The nonrelativistic energy equation was obtain by applying nonrelativistic limit to the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 73 publications
(91 reference statements)
2
26
0
1
Order By: Relevance
“…A similar trend is observed for energy variation with quantum number, l. This is consistent with the results in Table 3 (see Figure 3). Figures 4,5,6,7,8,9,10,11,12, and 13 are plots showing variations of various thermodynamic properties of the diatomic molecules with the temperature parameter, β, and the upper bound vibrational quantum number, λ. In Figure 4, the partition function, Z, increases as β increases for the Cl 2 molecule, but decreases for the N 2 molecule.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar trend is observed for energy variation with quantum number, l. This is consistent with the results in Table 3 (see Figure 3). Figures 4,5,6,7,8,9,10,11,12, and 13 are plots showing variations of various thermodynamic properties of the diatomic molecules with the temperature parameter, β, and the upper bound vibrational quantum number, λ. In Figure 4, the partition function, Z, increases as β increases for the Cl 2 molecule, but decreases for the N 2 molecule.…”
Section: Resultsmentioning
confidence: 99%
“…The significance of spin and pseudospin symmetries in Dirac equation and their contributions in nuclear and Hadron physics is worthy of note [ 1 , 2 , 3 , 4 ]. As a result, some authors have discussed Dirac equation under various interactions [ 5 , 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Greene-Aldrich approximation scheme is mostly applicable for short range potentials [7]. Eigensolutions for both relativistic and nonrelativistic wave equations have been studied with different methods which include the following: Exact quantisation, WKB, Nikiforov-Uvarov method (NU), Laplace transform technique, asymptotic iteration method, proper quantisation, supersymmetric quantum mechanics approach, vibrational approach, formula method, factorisation method, and Shifted 1/N-expansion method [8][9][10][11][12][13]. Bound state solutions obtained from the Schrödinger equation has practical applications in investigating tunnelling rate of quantum mechanical systems [14] and mass spectra of quarkonia systems [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Cao et al, [56], studied the TPs of light mesons, including the temperature dependence of their masses by solving the spatial correlation. In recent times scholars, have proposed new potentials through the combination of two potentials [57,58]. It's observed that the combination of at least two potential models has a propensity to fit experimental data more than a single potential [55].…”
Section: Introductionmentioning
confidence: 99%